Case Report: Chronic Bacterial Prostatitis Treated With Phage Therapy After Multiple Failed Antibiotic Treatments - Johri, Apurva Virmani; Johri, Pranav; Hoyle, Naomi; Pipia, Levan; Nadareishvili, Lia; Nizharadze, Dea (Frontiers in Pharmacology, 2021)
Background: Chronic Bacterial Prostatitis (CBP) is an inflammatory condition caused by a persistent bacterial infection of the prostate gland and its surrounding areas in the male pelvic region. It is most common in men under 50 years of age. It is a long-lasting and debilitating condition that severely deteriorates the patient’s quality of life. Anatomical limitations and antimicrobial resistance limit the effectiveness of antibiotic treatment of CBP. Bacteriophage therapy is proposed as a promising alternative treatment of CBP and related infections. Bacteriophage therapy is the use of lytic bacterial viruses to treat bacterial infections. Many cases of CBP are complicated by infections caused by both nosocomial and community acquired multidrug resistant bacteria. Frequently encountered strains include Vancomycin resistant Enterococci, Extended Spectrum Beta Lactam resistant Escherichia coli, other gram-positive organisms such as Staphylococcus and Streptococcus, Enterobacteriaceae such as Klebsiella and Proteus, and Pseudomonas aeruginosa, among others. Case Presentation: We present a patient with the typical manifestations of CBP. The patient underwent multiple courses of antibiotic treatment without any long-term resolution of his symptoms. Testing of prostatic secretion and semen samples revealed pathogenic bacteria in each case, which collectively included members of the Staphylococcal species such as Methicillin resistant Staphylococcus aureus (MRSA) and Staphylococcus haemolyticus, Enterococcus faecalis, and Streptococcus mitis, among others. Methods and Outcome: Bacteriophage preparations from the Eliava Institute were used to treat the patient after establishing phage sensitivity to the pathogenic bacteria. Significant improvements in symptoms and re-testing of samples after bacteriophage treatment indicated a reduction in the bacterial load and resolution of the infection. Discussion: The patient saw significant improvement of symptoms, and positive dynamics in bacterial titres and ultrasound controls after phage therapy. The failure of antibiotic therapy and subsequent success of bacteriophage therapy in treating chronic bacterial prostatitis shows the effectiveness of bacteriophages in controlling chronic infections in areas of low vascularity and anatomical complexity. These cases also highlight the efficacy of phages in overcoming antibiotic-resistant infections as well as biofilm infections.